AN ANALYSIS OF ORTHOGRAPHIC AND LEXICAL ERRORS IN WRITTEN ARABIC: ANALISIS KESALAHAN ORTOGRAFIS DAN LEKSIKAL DALAM PENULISAN BAHASA ARAB - Nuraini Iqomi Sholawati; Anggi Baity; Fauda Zakiyah Anafiha Nusantara; Umi Dzakiyatun Niswatin (Muaddib: Journal of Arabic Language and Literature, 2025)
Mastery of writing in Arabic is closely related to students’ ability to use accurate vocabulary and orthographic rules, since both aspects are essential for developing overall language skills. However, in practice, various orthographic and lexical errors are still commonly found, which affect students’ writing proficiency. This study aims to identify the types of orthographic and lexical errors in Arabic writing and to analyze the underlying factors. The research employed a descriptive qualitative method with a case study approach involving grade XI students of MAN 1 Kota Kediri. Data were collected through document analysis, interviews, observations, and writing tests, and then analyzed to uncover patterns of errors and their causes. The findings reveal four main types of errors: incorrect letter writing, misuse of diacritical marks (harakat), improper letter connections, and inappropriate word choice. The contributing factors include students’ limited mastery of basic Arabic, lack of fine motor skills, monotonous teaching methods, limited learning time, and insufficient access to learning resources. Based on these results, the study recommends the application of more contextual teaching strategies, the provision of intensive writing practice, and the creation of a more supportive learning environment to enhance students’ writing skills.